2013
DOI: 10.3324/haematol.2013.092460
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risks after splenectomy among 8,149 cancer-free American veterans: a cohort study with up to 27 years follow-up

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nveterans who underwent splenectomy with a follow-up of up to 27 years. In this cohort, we assessed patterns of hospitalization for infections, thromboembolism, and malignancies following splenectomy. Methods Study populationBased on USA census data, an estimated 30 million veterans were entitled to admission to VA hospitals during the study period. 33 The VA database has been previously described. 34,35 In the present study, splenectomized patients were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
219
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(239 citation statements)
references
References 45 publications
4
219
2
5
Order By: Relevance
“…However, total splenectomy exposes the patient to a life -long risk of potentially lethal infections (17) and thus, its usage was reconsidered. In children less than 5 years old, the risk of overwhelming postsplenectomy sepsis may be increased 60-to 100 fold, compared with that of children without a splenectomy (18) There are also concerns that despite the immunizations against encapsulated bacteria and the postoperative antibiotic prophylaxis, the risk after total splenectomy is never eliminated.…”
Section: The Role Of Splenectomy In Hereditary Spherocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, total splenectomy exposes the patient to a life -long risk of potentially lethal infections (17) and thus, its usage was reconsidered. In children less than 5 years old, the risk of overwhelming postsplenectomy sepsis may be increased 60-to 100 fold, compared with that of children without a splenectomy (18) There are also concerns that despite the immunizations against encapsulated bacteria and the postoperative antibiotic prophylaxis, the risk after total splenectomy is never eliminated.…”
Section: The Role Of Splenectomy In Hereditary Spherocytosismentioning
confidence: 99%
“…In children less than 5 years old, the risk of overwhelming postsplenectomy sepsis may be increased 60-to 100 fold, compared with that of children without a splenectomy (18) There are also concerns that despite the immunizations against encapsulated bacteria and the postoperative antibiotic prophylaxis, the risk after total splenectomy is never eliminated. (17,19,20) Because of this reason, a number of alternatives to total splenectomy have been considered, including auto-transplantation of the removed spleen and partial splenectomy. (21) The use of partial splenectomy, particularly in pediatric patients, aims to retain splenic immunologic function, while at the same time to decrease the rate of hemolysis.…”
Section: The Role Of Splenectomy In Hereditary Spherocytosismentioning
confidence: 99%
“…Red cells from SCD and splenectomized patients were trypsin-treated and stained with R10, and also found to have elevated levels of internal GPA-decorated vesicles ( Figure 2E-F). We provide evidence indicating that PS-exposed red cells described in SCD and splenectomized individuals [9][10][11][12] are circulating reticulocytes, which cannot be properly processed because the patients lack a functional spleen.…”
mentioning
confidence: 99%
“…Recent study conducted by Nived et al showed that the number of patients who have received pneumococcal vaccine is lower than the number of patients in our study (81%); however, a larger number of patients received the vaccines against Haemophilus influenzae and meningococcal vaccine (51,9% and 22,8 %, respectively) (12). The importance of vaccination has also been shown by a study conducted in the USA (13). This study showed that splenectomized patients are at higher risk of pneumonia, meningitis and septicemia, even 10 years after splenectomy (13).…”
Section: Discussionmentioning
confidence: 53%
“…The importance of vaccination has also been shown by a study conducted in the USA (13). This study showed that splenectomized patients are at higher risk of pneumonia, meningitis and septicemia, even 10 years after splenectomy (13). It is alarming that none of the doctors (surgeons, general practitioners) knew about the use of vaccines for Neisseria meningitides and Haemophilus influenzae after splenectomy.…”
Section: Discussionmentioning
confidence: 97%